Impaired T-cell responses to sphingosine-1-phosphate in HIV-1 infected lymph nodes - Mudd, Joseph C. (American Society of Hematology, 2013)
The determinants of HIV-1-associated lymphadenopathy are poorly understood. We hypothesized that lymphocytes could be sequestered in the HIV-1+ lymph node (LN) through impairments in sphingosine-1-phosphate (S1P) responsiveness. To test this hypothesis, we developed novel assays for S1P-induced Akt phosphorylation and actin polymerization. In the HIV-1+ LN, naïve CD4 T cells and central memory CD4 and CD8 T cells had impaired Akt phosphorylation in response to S1P, whereas actin polymerization responses to S1P were impaired dramatically in all LN maturation subsets. These defects were improved with antiretroviral therapy. LN T cells expressing CD69 were unable to respond to S1P in either assay, yet impaired S1P responses were also seen in HIV-1+ LN T cells lacking CD69 expression. Microbial elements, HIV-1, and interferon α – putative drivers of HIV-1associated immune activation all tended to increase CD69 expression and reduce T-cell responses to S1P in vitro. Impairment in T-cell egress from lymph nodes through decreased S1P responsiveness may contribute to HIV-1-associated LN enlargement and to immune dysregulation in a key organ of immune homeostasis.